The Acute and Late Toxicities of MRI-Guided External Beam Partial Breast Irradiation Delivered Using a Once-Per-Day Regimen - Lee, Hye In; Kim, Kyubo; Kim, Jin Ho; Chang, Ji Hyun; Shin, Kyung Hwan (Frontiers in Oncology, 2021)
Background and purpose The use of external beam accelerated partial breast irradiation (APBI) using a twice-per-day regimen has raised concerns about increase rates of late toxicities. We compared toxicity outcomes of external beam APBI using a once-per-day regimen and accelerated hypofractionated whole breast irradiation (AWBI) in patients with early-stage breast cancer. Materials and Methods This was a single-institution, retrospective cohort study. Patients aged ≥50 years with pTisN0 or pT1N0 breast cancer who underwent breast-conserving surgery and adjuvant radiotherapy were included. APBI was delivered at 38.5 Gy in 10 fractions once daily using magnetic resonance imaging (MRI)-guided radiotherapy only to patients who were strictly “suitable”, according to the ASTRO-APBI guidelines. AWBI was delivered at 40.5–43.2 Gy in 15 or 16 fractions with or without a boost. Results Between October 2015 and December 2018, 173 and 300 patients underwent APBI and AWBI, respectively. At a median follow-up of 34.9 months (range 7.1 to 55.4 months), the 3-year recurrence-free survival rates of the APBI and AWBI groups were both 99.2% (p=0.63). Acute toxicities were less frequent in the APBI than AWBI group (grade 1: 95 [54.9%] vs. 233 [77.7%] patients; grade 2: 7 [4.0%] vs. 44 [14.7%] patients; no grade ≥3 toxicities were observed in either group, p<0.001). Late toxicities were less common in the APBI than AWBI group (grade 1: 112 [64.7%] vs. 197 [65.7%] patients; grade 2: 9 [5.2%] vs. 64 [21.3%] patients; grade 3: 0 vs. 5 [1.7%] patients, p<0.001). Multivariate analysis showed that APBI was significantly associated with fewer late toxicities of grade ≥2 compared with AWBI (odds ratio 4.17, p=0.006). Conclusion Once-per-day APBI afforded excellent locoregional control and fewer toxicities compared with AWBI. This scheme could be an attractive alternative to AWBI in patients who meet the ASTRO-APBI guidelines.